Analisis Hukum Sistem Gantang Bibit Padi Di Desa Sungai Nilam Dalam Persektif Kitab Al-Umm Imam Syafi'i - Ilma Ilma; Moch. Riza Fahmi; Ari Widiyawati (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2025)
The objectives of this study are: 1) To understand the practice of the paddy seed gantang system carried out by the community of Sungai Nilam Village; and 2) To determine the legal status of the paddy seed gantang system in Sungai Nilam Village from the perspective of Imam Syafi’i’s Al-Umm. The research method used was field research with a descriptive-qualitative approach. This study used primary data sources in the form of in-depth interviews. Secondary data sources were translations of Imam Syafi'i's Kitab Al-Umm. Data collection techniques were carried out through structured interviews and document studies. Data validity techniques used source and technique triangulation. Data analysis techniques consisted of data collection, data reduction, data presentation, and conclusion drawing. The results showed that: 1) the practice of the paddy seed gantang system is a tradition passed down from generation to generation that reflects the values of mutual cooperation, carried out through the exchange of similar goods using the same measure, even though there is an imbalance in the quality of the goods; 2) from the perspective of the Book of Al-Umm by Imam Syafi'i, it is in accordance with the provisions of muqayadhah, but does not fully meet the requirements due to differences in the quality of goods. However, this practice remains relevant to the principles of muamalah in Islam, which emphasizes justice.